If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2x + -1) = 7x + 54 Reorder the terms: 6(-1 + 2x) = 7x + 54 (-1 * 6 + 2x * 6) = 7x + 54 (-6 + 12x) = 7x + 54 Reorder the terms: -6 + 12x = 54 + 7x Solving -6 + 12x = 54 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -6 + 12x + -7x = 54 + 7x + -7x Combine like terms: 12x + -7x = 5x -6 + 5x = 54 + 7x + -7x Combine like terms: 7x + -7x = 0 -6 + 5x = 54 + 0 -6 + 5x = 54 Add '6' to each side of the equation. -6 + 6 + 5x = 54 + 6 Combine like terms: -6 + 6 = 0 0 + 5x = 54 + 6 5x = 54 + 6 Combine like terms: 54 + 6 = 60 5x = 60 Divide each side by '5'. x = 12 Simplifying x = 12
| 99x+999y=10 | | X^2+86x+105=0 | | -7+-u=3 | | 9x-4(5x-3)= | | -4+5(-2r)-81= | | -3w^2-8w+3=0 | | 16p+q-10p+5q= | | 3x^3+12x^2-96x=0 | | 30y=5x+104 | | 8t^2+16t=42 | | (X+10)+50=x | | 30=5x+104 | | v=3.14r*3.14h | | 38+8= | | 5x-3=9x+33 | | a=pi*r^2 | | X-10+y+3x=180 | | 3v^2+11=6v | | N+5.5=-4.5 | | 26*p=233 | | 10-5=25+10 | | 7x+25=3x+5 | | 4-(sec^2)(x)=0 | | bx=cforx | | 5x-7y=3x+y | | y=x^2+7x+32 | | A+15=233 | | 4r^2=64 | | ax+b=5(x-a) | | 10-(3z)=37 | | 5x=-12+4y | | X+2(x+3)=23 |